Experimental evaluation of the wind effects on an operating power transmission tower - Carvalho,Hermes (2016)
Abstract Static and dynamic effects on power transmission towers can be evaluated by methodologies available in codes, which suggest the use of linear static analysis. By using numerical simulations, it is possible to observe the strong influence of the geometric nonlinear behavior of transmission cables. Dynamic effects also strongly influence this behavior, with the possibility of resonance between the cables and the structure, but up to the moment, the existent analysis procedures have not been completely validated on an experimental basis. In order to validate a complete analysis methodology, experimental procedures are proposed for a suspension tower of a 138kV transmission line in use. A tridimensional anemometer was installed on this structure in order to measure the values and directions of wind speeds. Simultaneous strain values were collected on the main elements of the tower through optical extensometers. Optical sensor technology with Fiber Bragg Gratings was used, due to the characteristic of immunity to the electromagnetic field occasioned by high electric currents. The string swing angle was evaluated through a high-resolution camera and a tridimensional accelerometer. With this instrumentation, it is possible to create a complete database that correlates wind speeds with the responses of the structural set. At the moment, 5 months of data have been collected and the instrumentation is in the final testing phase and synchronized. After this step, real-time measurements will be performed.